Effectiveness of problem-based learning combined with lecture based learning methodology in renal pathology education - Xu, Guoshuang; Zhao, Lijuan; Zhou, Meilan (Cogent Education, 2023)
To evaluate the teaching effect of problem-based learning (PBL) combined with lecture-based learning (LBL) compared with that of LBL alone in renal pathology education for trainees receiving standardized training.A total of 65 undergraduate medical students who received standardized training in Xijing Hospital from January 2016 to November 2019 were randomly divided into a PBL+LBL group (33 subjects) and an LBL alone group (32 subjects). The teaching effect was evaluated using the subjects' diagnostic accuracy of renal pathology, knowledge of renal pathology and teaching satisfaction assessment. The diagnostic accuracy of renal pathology, knowledge of renal pathology and teaching satisfaction assessment in PLB+LBL group (81.0%, 79.99 ± 6.65 and 89.4%, respectively) were significantly higher than those in the LBL alone group (58.5%, 62.89 ± 10.31 and 58.9%, respectively). While teaching renal pathology to undergraduate medical students receiving standardized training, the PBL+LBL group benefited from a teaching effect and gave a better teaching satisfaction.